2017
DOI: 10.1007/s10826-016-0642-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Placement History and Current Family Environment in Children’s Aggression in Foster Care

Abstract: Predictors of the physical and relational aggressive behavior of children in foster care were examined (N = 160, 50.9% male, M age = 7.57, SD = 2.39). First, predictors representative of children’s placement histories were examined in relation to the children’s aggression at T1. Next, predictors representing characteristics of the current family environment were examined in relation to the children’s aggression at T2 (four months later). Results revealed that a greater number of prior group home placements and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…This study is based only on the residential care context and does not take other types of institutionalization and/or adoption into account. Prior research has also demonstrated a link between frequent changes in foster placements and increased behavior problems (Perry & Price, 2017), and considering this information in subsequent studies would be very interesting.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 96%
“…This study is based only on the residential care context and does not take other types of institutionalization and/or adoption into account. Prior research has also demonstrated a link between frequent changes in foster placements and increased behavior problems (Perry & Price, 2017), and considering this information in subsequent studies would be very interesting.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 96%
“…Aggression, which is often defined as hostile, destructive, or injurious behavior, has the potential to cause serious harm to others (Hamama and Arazi 2012 ; Ho et al 2010 ; Tonnaer et al 2019 ). Youth in foster care tend to have higher levels of behavior problems, including aggression, compared to their peers in the general community (Keller et al 2001 ; Perry and Price 2017 ; Tarren-Sweeney 2008 ). One study focused on determining the clinical status of children in state custody found that 34 % of youth were rated as having significant behavior problems, with the greatest numbers meeting the clinical range for aggressive, delinquent, and withdrawn behaviors (Heflinger et al 2000 ).…”
Section: Thought Problems and Aggression Over Time Among Youth In Foster Carementioning
confidence: 99%
“…One study focused on determining the clinical status of children in state custody found that 34 % of youth were rated as having significant behavior problems, with the greatest numbers meeting the clinical range for aggressive, delinquent, and withdrawn behaviors (Heflinger et al 2000 ). Aggressive behaviors may result in youths’ social challenges and inform long-term consequences, such as psychopathology and incarceration (Henggeler and Sheidow 2003 ; Perry and Price 2017 ).…”
Section: Thought Problems and Aggression Over Time Among Youth In Foster Carementioning
confidence: 99%
“…Predictor variables included the presence of various maltreatment types, total maltreatment score, and the number of adverse individual- and family-level experiences. We considered controls among sociodemographics (e.g., current age, services received in the last year) and placement variables (e.g., age when first placed in out-of-home care, number of caregiver changes, current placement type, length of time living with current caregiver) that have been linked with some of the outcomes examined (Chow, Mettrick, Stephan, & Von Waldner, 2014; Farmer et al, 2010; O’Higgins et al, 2017; Perry & Price, 2017; Rock, Michelson, Thomson, & Day, 2015) and/or that would seem reasonable to include because of their potential impact on youth well-being and functioning (e.g., number of placement changes and youth–caregiver relationship). In the end, we included current age, age at child welfare entry, and number of caregiver changes in analyses because they were significantly correlated with predictor and outcome variables.…”
Section: Data Analysesmentioning
confidence: 99%